Preliminary diagnosis of environmental costs at an industrial unit of a food sector company in Passo Fundo, RS - Brandli, Elisangela Nicoloso; Pandolfo, Adalberto; González, Marco Aurélio; Reinehr, Renata; Guimarães, Jalusa; Barbisan, Ailson (Revista Gestão da Produção Operações e Sistemas, 2008)
This article presents a preliminary diagnosis of the decurrent ambient costs of the productive process of a food company.. The work was carried through from bibliographical revisions, to identify to the variable and pointers related to the ambient costs and to define the methodology to be applied throughout the research. Another used strategy in had been visits leases, as well as interviews not structuralized and analyses of reports of exit of residues, ambient reports of identification of aspects and impacts, reports of ambient pointers and flowcharts of the productive process, disponibilizados for the company. The results gotten until the moment indicate that the countable system used by the company does not present pointers adjusted for the effective control of the investments and expenses in the area of the environment. For the scientific community the present study it will bring greater knowledge on ambient costs, giving subsidies to other companies of as to proceed in the identification process of its ambient costs, since still it is data little explored in Brazil and has few research related to the subject. Keywords: Productive process. Decision making. Countable system. Methodology Jasch.